Objeto del proceso contencioso administrativo en el Perú - Mac Rae Thays, Elizabeth Roxana (2020)
This article discusses the development of the contentious administrative process in Peru, commenting in part on its scope and objective as a mechanism to protect the rights and interests of individuals before the Public Administration. In part, the historical development that this figure has had during the last years will be described, as well as the modifications that it has undergone since its enactment in Peru.